2021
DOI: 10.1007/s11657-021-00891-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of sequential daily teriparatide/weekly alendronate compared with alendronate monotherapy for older osteoporotic women with prior vertebral fracture in Japan

Abstract: Summary Using a Markov microsimulation model among hypothetical cohorts of community-dwelling older osteoporotic Japanese women with prior vertebral fracture over a lifetime horizon, we found that daily subcutaneous teriparatide for 2 years followed by weekly oral alendronate for 8 years was not cost-effective compared with alendronate monotherapy for 10 years. Purpose Teriparatide has proven efficacy in reducing osteoporot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Mori et al, studying a Japanese population of older osteoporotic women with prior vertebral fractures compared sequential teriparatide (2 years) followed by alendronate for 8 years, versus alendronate monotherapy. They found, again, that cost-effectiveness was very sensitive to treatment acquisition costs, only becoming cost effective with price discounts to teriparatide of 85%, 50%, and 15% at ages 70, 75, and 80 years, respectively, compared to the current biosimilar cost [ 135 ].…”
Section: Cost-effectiveness Of Sequential Treatmentsmentioning
confidence: 99%
“…Mori et al, studying a Japanese population of older osteoporotic women with prior vertebral fractures compared sequential teriparatide (2 years) followed by alendronate for 8 years, versus alendronate monotherapy. They found, again, that cost-effectiveness was very sensitive to treatment acquisition costs, only becoming cost effective with price discounts to teriparatide of 85%, 50%, and 15% at ages 70, 75, and 80 years, respectively, compared to the current biosimilar cost [ 135 ].…”
Section: Cost-effectiveness Of Sequential Treatmentsmentioning
confidence: 99%
“…Evidence accumulated over the past decade supports that sequential therapy with the initiation of anabolic treatment followed by antiresorptive treatment improves health-related quality-of-life outcomes for individuals with osteoporosis ( 47 ) and our current study reinforces this strategy from the health economic points of view. In the earlier published work, one of the authors of the current study compared sequential daily teriparatide/weekly alendronate with alendronate monotherapy in older osteoporotic women with a prior vertebral fracture in the US ( 18 ) and Japan ( 19 ). Both studies demonstrated that even with the availability of generic teriparatide, sequential teriparatide/alendronate would not be cost-effective unless the cost of generic teriparatide was largely discounted compared with the brand one.…”
Section: Discussionmentioning
confidence: 99%
“…In real-world practice, persistence and compliance with osteoporosis treatments are reported to be imperfect ( 37 , 38 ). We considered drug persistence and compliance during the therapy based on our published papers in the Japanese or Chinese populations ( 12 , 19 ). Compliance rates with teriparatide and zoledronic acid were higher in clinical than observational studies.…”
Section: Methodsmentioning
confidence: 99%
“…Although in our model the teriparatide strategy had a better therapeutic effect than the no treatment including our assumption that teriparatide reduced the risk of hip fracture, 18,42 the drug cost of teriparatide was estimated to be so expensive even after the adoption of PAP that the ICER of teriparatide compared with no treatment remarkably exceeded the threshold. In this study, we set up two years of the treatment period for teriparatide as there are safety concerns with teriparatide use beyond two years, 21 whereas three years of treatments were provided in the other three injected medications.…”
Section: Economics Of Injected Antiosteoporotic Drugsmentioning
confidence: 93%